The Climatic Impact of Shallow and Deep Troughs During the 2004-2005 Season Over Iraq - Kareem Ahmed AL-abiea, Assist. Lect. Naba’’; Al-Huda Abdul Rahman Habib, Assist .Lect. Nour (Basra studies journal, 2024)
This study examines the meteorological effects of shallow and deep troughs based on daily readings for the season from September 2004 to August 2005. It focuses on normal temperatures, atmospheric pressure, and relative humidity at 12:00 PM GMT, analyzing the types of shallow and deep troughs at 1000 and 850 millibar levels through weather map analysis (12:00 PM GMT). The research monitors the Siberian, European, and subtropical highs over Mosul, Baghdad, and Basra, highlighting fewer days of secondary center trough persistence contrasted with increased days of deep and shallow trough extensions. These trough patterns significantly impact Iraq’s climate, leading to higher temperatures, lower relative humidity, varied precipitation patterns, drought, and increased atmospheric pressure values.